Thinking how to live - Gibbard, Allan (Cambridge, Mass. : Harvard University Press, 2003)
"Philosophers have long suspected that thought and discourse about what we ought to do differ in some fundamental way from statements about what is. But the difference has proved elusive, in part because the two kinds of statement look alike. Focusing on judgments that express decisions - judgments about what is to be done, all things considered - Allan Gibbard offers a compelling argument for reconsidering, and reconfiguring, the distinctions between normative and descriptive discourse - between question of "ought" and "is."" "Gibbard considers how our actions, and our realities, emerge from the thousands of questions and decisions we form for ourselves. The result is a book that investigates the very nature of the questions we ask ourselves when we ask how we should live, and that clarifies the concept of "ought" by investigating the patterns of normative concepts involved in beliefs and decisions."--Jacket
I: Preliminaries -- 1/ Introduction: a possibility proof -- 2. Intuitionism as template: emending Moore -- II: The thing to do -- 3. Planning and ruling out: the Frege-Geach problem -- 4. Judgment, disagreement, negation -- 5. Supervenience and constitution -- 6. Character and import -- III: Normative concepts -- 7. Ordinary oughts: meaning and motivation -- 8. Normative kinds: patterns of engagement -- 9. What to say about the thing to do: the expressivistic turn and what it gains us -- IV: Knowing what to do -- 10. Explaining with plans -- 11. Knowing what to do -- 12. Ideal response concepts -- 13. Deep vindication and practical confidence -- 14. Impasse and dissent
Includes bibliographical references (pages 289-294) and index
Keywords: Expressivism (Ethics); Normativity (Ethics)